Anticholinergic Medication Use, Dopaminergic Genotype, and Recurrent Falls. (16th December 2020) - Rosso, Andrea; Zhu, Xiaonan; Marcum, Zachary; Bohnen, Nico; Sprague, Briana; Rosano, Caterina
Abstract: Anticholinergic medications (A-chol) increase risk for falls; higher dopaminergic signaling may provide resilience to these effects. In 2489 older adults (mean age=74; 52% women) with 10 years of data on medication use, falls, and dopaminergic genotype (catechol-O-methyltransferase (COMT)), we assessed the association of A-chol use with recurrent falls (≥2) over the subsequent 12 months using generalized estimating equations. Effect modification by COMT (met/met, higher dopamine signaling, n=473 vs val carriers, lower dopamine signaling, n=2016) was tested; analyses were then stratified by COMT and adjusted for demographics and A-chol use indicators. During follow-up, 843 people reported recurrent falls. A-chol use doubled the odds of recurrent falls (OR [95%CI]=2.13[1.74, 2.60]), with a suggested effect modification by COMT (p=0.1). The association was present in val carriers (adjusted OR [95%CI]=1.93[1.36, 2.73]) but not in met/met (adjusted OR [95%CI]=1.30[0.53, 3.22]). Higher dopaminergic signaling may provide protection against the effects of A-chol use on fall risk.